Risk Factors of Pulmonary Tuberculosis: A Case-Control Study from Eastern Indonesia - Haposan Simatupang; Sarce Makaba; Hasmi; Semuel Piter Irab; Yacob Ruru; Muhammad Nurdin Akbar (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Pulmonary Tuberculosis (TB) remains a major public health concern in Indonesia, including in Teluk Bintuni District. The increasing trend of cases underscores the urgency of identifying risk factors, particularly in underserved areas. This study aimed to analyze risk factors associated with pulmonary TB incidence in Teluk Bintuni. A quantitative case-control (1:2) was applied, involving 336 purposively selected respondents who sought care between January and December 2024. Cases were confirmed TB patients, and controls were non-TB patients. Secondary data were obtained from the Tuberculosis Information System (Sistem Informasi Tuberkulosis or SITB) and health center records. Univariate analysis indicated that most pulmonary tuberculosis cases were observed among respondents with lower education, productive age group, non-smokers, and Papuan ethnicity. Bivariate analysis using chi-square and Fisher’s exact tests identified variables with p<0.25 for inclusion in multivariate logistic regression. Significant associations were found between TB and HIV status, education, distance to health facilities, and ethnicity. HIV positivity was observed in 12.5% of cases versus 3.1% of controls (p=0.001; OR=4.429). Low education was more common among controls (79.5%) than cases (55.4%) (p<0.001;OR=0.320), non-Papuan ethnicity accounted for 25.0% of cases and 8.5% of controls (p<0.001; OR=0.278). Living ≥5 km from health services was less frequent among cases (14.3%) than controls (24.1%) (p=0.037; OR=0.525). In multivariate analysis, HIV status, ethnicity, and education remained significant, with HIV status emerging as the strongest predictor (OR=4.376; p=0.003). The lower TB prevalence among individuals with less-education may reflect underdiagnosis due to limited access to service or reduced or care-seeking. These findings highlight the need for HIV control, improved detection, and culturally tailored TB strategies in remote communities.